Interaction of the pathogenic mold Aspergillus fumigatus with lung epithelial cells - Osherov, Nir (Frontiers in Microbiology, 2012)
Aspergillus fumigatus is an opportunistic environmental mold that can cause severe allergic responses in atopic individuals and poses a life-threatening risk for severely immunocompromised patients. Infection is caused by inhalation of fungal spores (conidia) into the lungs. The initial point of contact between the fungus and the host is a monolayer of lung epithelial cells. Understanding how these cells react to fungal contact is crucial to elucidating the pathobiology of Aspergillus-related disease states. The experimental systems, both in vitro and in vivo, used to study these interactions, are described. Distinction is made between bronchial and alveolar epithelial cells. The experimental findings suggest that lung epithelial cells are more than just “innocent bystanders” or a purely physical barrier against infection. They can be better described as an active extension of our innate immune system, operating as a surveillance mechanism that can specifically identify fungal spores and activate an offensive response to block infection. This response includes the internalization of adherent conidia and the release of cytokines, antimicrobial peptides and reactive oxygen species. In the case of allergy, lung epithelial cells can dampen an over-reactive immune response by releasing anti-inflammatory compounds such as kinurenine. This review summarizes our current knowledge regarding the interaction of A. fumigatus with lung epithelial cells. A better understanding of the interactions between A. fumigatus and lung epithelial cells has therapeutic implications, as stimulation or inhibition of the epithelial response may alter disease outcome.